The Influence of Islamic Economic Law on Sustainable Development in Developing Countries - Ariyanti, Rini; Lima, Lucas; Costa, Tiago; Silva, Pedro; Sucipto, Bambang (Sharia Oikonomia Law Journal, 2024)
In today’s era of globalization, it is important for developing countries to achieve sustainable development. However, sustainable development requires consideration of social, cultural, and environmental perspectives in addition to economic ones. Islamic economic law emerges as an alternative solution amidst this complexity, offering principles that promote a balance between economic growth and social justice. This study aims to comprehensively analyze the impact of Islamic economic law on sustainable development in developing countries. This involves analyzing how the principles of the law are applied in the economic activities of these countries, as well as how they impact aspects of sustainable development such as social stability, poverty alleviation, environmental preservation, and inclusive economic growth. In this study, qualitative methods will be used to investigate the literature and analyze the comparison of developing countries that implement Islamic economic law at various levels. Data will be collected from primary and secondary sources, including financial reports, legal documents, and case studies on the implementation of Islamic economic law in certain countries. Studies show that the implementation of Islamic economic law benefits sustainable development in developing countries. Sustainability, justice, and economic and social balance have been shown to promote inclusive economic growth, improved social welfare, and more sustainable management of natural resources.